2003
DOI: 10.28945/319
|View full text |Cite
|
Sign up to set email alerts
|

Computer Technology Awareness by Elementary School Teachers: A Case Study from Turkey

Abstract: Executive SummaryIn this study, teachers' perspectives, their awareness level of specific technologies and the roles this technology plays in education are researched. Technical problems that inhibited the use of computers in their schools are also identified. Data was elicited from a sample of 252 teachers who were working in basic education schools in Trabzon, Turkey.The results revealed that many teachers were not computer users. Many teachers lacked a functional computer literacy foundation upon which to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 5 publications
1
20
0
4
Order By: Relevance
“…As a consequence, some training on the use of advanced technology for teachers should be taken into account by the teacher educators, the schools, and even the policy makers. These classroom challenges are aligned with Asan (2003) and Buabeng-Andoh (2012) who found out that teachers' lack of technological competence which involves lack of hardware, lack of knowledge and skills about using computers, lack of training or insufficient training opportunities, lack of teachers' confidence and crowded classrooms were determined as the most important problems faced by the teachers.…”
Section: Pedagogical Implications On Efl Teaching and Learningmentioning
confidence: 59%
See 1 more Smart Citation
“…As a consequence, some training on the use of advanced technology for teachers should be taken into account by the teacher educators, the schools, and even the policy makers. These classroom challenges are aligned with Asan (2003) and Buabeng-Andoh (2012) who found out that teachers' lack of technological competence which involves lack of hardware, lack of knowledge and skills about using computers, lack of training or insufficient training opportunities, lack of teachers' confidence and crowded classrooms were determined as the most important problems faced by the teachers.…”
Section: Pedagogical Implications On Efl Teaching and Learningmentioning
confidence: 59%
“…The limitation was shown due to the fact that, apart from the lesson using a video, the EFL teachers merely deployed Ppt which focused on simple pictures or written explanation with no movement or sounds on the slides during the observation. This is aligned with Asan (2003) who discovered that many teachers lacked a functional computer literacy foundation upon which to build new technology and skills, such as lack of knowledge and skills about using computers and insufficient training opportunities.…”
Section: Correspondence Between Efl Teachers' Cognitions and Their Vomentioning
confidence: 62%
“…The studies of Velez (1998), Asan (2005) and Markova, et. al (2003) contradict the result of this study because it showed a significant difference on the awareness level of the respondents when classified as to sex.…”
Section: Inferential Data Analysismentioning
confidence: 98%
“…Other definitions of computer literacy focus on two areas: "whatever a person needs to know and do with computers in order to function competently in our society" and "a measure of competency to exploit computer technology" (Halaris & Sloan, 1985). The search for computer literacy has its beginning in elementary school (Albee, 2003;Asan, 2003) and continues through high school. In addition, computer literacy has now become a global issue (Asan, 2003;Csapo, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The search for computer literacy has its beginning in elementary school (Albee, 2003;Asan, 2003) and continues through high school. In addition, computer literacy has now become a global issue (Asan, 2003;Csapo, 2002).…”
Section: Introductionmentioning
confidence: 99%